Srī Gurū Grantha Sāhiba : bāṇī-prabandha dī jugāta dā ankaṛā-kosha / Baladewa Siṅgha Cīmā, Kanwara Dīpa Siṅgha = Sri Guru Granth Sahib, bani di jugat da ankara kosh / by Kanwardeep Singh, Dr. Baldev Singh Cheema. - Cīmā, Baladewa Siṅgha; Kam̆wara Dīpa Siṅgha (Ludhiāṇā : Cetanā Prakāshana, 2015)
Form and structure of Adi-Granth, Sikh canon.
In Panjabi.
Keywords: Ādi-Granth -- Criticism, interpretation, etc; Ādi-Granth.; Criticism, interpretation, etc